Pengaruh Unsur Military Terhadap Desain Fashion Kalangan Muda di Indonesia - Benhart Bhara Menoreh; Sulistyo Setiawan (Jurnal Desain Indonesia., 2021)
Techwear is a fusion of fashion with outdoor outfit with a touch of military style, which focuses on function and prioritizes aspects of aesthetics and utility. The utility characteristics are more or less based on the form, silhouette and function of military uniform or all related to military. In its implementation, the product design results of this techwear are product designs that are inspired from aspects that exist in the military. After the research was conducted, there were several problems and opportunities from the scope of this techwear carrying facility, namely the need for product design means to bring fixgear bicycles to daily activities using fixgear bikes. With the characteristics of optimal fashion techwear, such as the Utility and Waterproof features, new opportunities arise about the means of carrying these techwear, which are inspired by the characteristics of fashion techwear and military look. In this aspect there is still plenty of room for deeper exploration in design and fashion. With the new fashion techwear emerging and developing in Indonesia, making the fashion trend interesting to be discussed deeper. This research was conducted using the Literature Study method which produced a review of relevant data.